ATENUASI MULTIPLE SEISMIK REFLEKSI LAUT MENGGUNAKAN METODE FILTERING RADON PADA PERAIRAN X - Murtiningtias Diah Ayu Martha Dewi; Oki Hedriana; Agus Setyawan (Youngster Physics Journal, 2016)
Multiple caused by waves that trapped in a layer of sea water or rock layers. The effect information propagation time longer effect as if there is a new layer, thus looping wave reflection. The existence of multiple noise is disruptive and even damaging that complicates intrepetasi in interpreting seismik that have focused so that multiple seismik cross sections obtained free of multiple. Methods in multiple energi weaken, one of them by using the filtering radon method which, in principle, filtering radon, radon transform of the data pre-stack time-offset domain (t-x) in the domain of p-tau (τ-p). In τ-p domain and the expected multiple primary signal can be distinguished by the speed difference moveoutnya. This study aims to evaluate the response of radon filtering is applied to the conventional method for multiple mengatenuasi. The results obtained from the radon showed multiple filtering methods reduced from previous conventional methods which showed multiple. It shows good effect radon filtering methods to weaken multiple.Keywords: multiple, Radon filtering, conventional method.